THU0190 Clinical outcomes among rheumatoid arthritis patients receiving adalimumab who did or did not participate in the patient support program: a subanalysis of the passion study. (12th June 2018) - Ostor, A.; Wassenberg, S.; Zueger, P.; Kalabic, J.; Wu, M.; Lagunes Galindo, I.; Van den Bosch, F.
Abstract : Background: The AbbVie Patient (pt) Support Program (PSP) is offered to pts prescribed adalimumab (ADA) for rheumatoid arthritis (RA) and other indications. Objectives: This subanalysis evaluated the impact of ADA in achieving clinical, functional, and pt-reported outcome treatment targets and sustained responses by PSP use. Methods: PASSION was a 78-wk postmarketing, multinational, observational study enrolling pts with moderate to severe RA receiving ADA in routine clinical care. Pts with an insufficient response to ≥1 disease modifying antirheumatic drug (DMARD; 1 prior biologic DMARD was allowed) and newly initiating ADA were enrolled. Pts were divided into 2 groups based on PSP participation: ever (PSP users) vs never (PSP non-users). Outcome measures included proportion of pts with low disease activity (LDA)/remission defined by Clinical Disease Activity Index (CDAI) ≤10, Simplified Disease Activity Index (SDAI) ≤11, and Disease Activity Score(DAS)28(C-reactive protein [CRP])≤3.2; proportion with mild to moderate disability (Health Assessment Questionnaire Disease Index [HAQ-DI] 0 to 1); and proportion with 20%/50%/70% improvement from baseline (BL) in ACR components (table 1). Missing values were imputed using last observation carried forward, and differences in proportions between PSP users and PSP non-users were compared with Chi-square tests. Results: Of 1025 pts treated with ADA in the study, 499 were PSP users and 526 were PSP non-users. A significantly greater proportion of PSP users vs PSP non-users had LDA/remission as defined by CDAI at wks 24, 52, and 78 and as defined by SDAI or DAS28(CRP) at weeks 52 and 78 (p<0.05 for all). A significantly greater proportion of PSP users vs PSP non-users also had mild to moderate disability defined by HAQ-DI at wk 78 (p=0.0239). Compared with PSP non-users, a significantly greater proportion of PSP users had 70% improvement from BL in PtGA, pain, and CRP at wks 24, 52, and 78; SJC28 at wks 52 and 78; and TJC28 and PhGA at wk 78 (table 1). At wks 24, 52, and 78, a significantly greater proportion of PSP users vs PSP non-users had 20% and 50% improvements from BL in all ACR components (all p<0.05), except for 50% improvement from BL in TJC28 at wks 24 and 78 and PhGA at wk 24. Conclusions: Among pts with moderate to severe RA initiating ADA treatment, participation in the PSP resulted in significantly greater improvements in clinical, functional, and pt-reported outcomes at wks 24, 52, and 78 in comparison to the PSP non-users. Acknowledgements: AbbVie funded the study and analysis, and approved the abstract for submission. Medical writing support was provided by Aric Fader, PhD, of Complete Publication Solutions, LLC (North Wales, PA, USA) and was funded by AbbVie. Disclosure of Interest: A. Ostor Grant/research support from: Lilly, Roche, MSD, AbbVie, Pfizer, Novartis, Janssen, and Bristol-Myers Squibb, Consultant for: Lilly, Roche, MSD, AbbVie, Pfizer, Novartis, Janssen, and Bristol-Myers Squibb, S. Wassenberg Grant/research support from: AbbVie, BMS, Fuji, Gilead, Novartis, Pfizer, Roche, Sandoz, and UCB, Consultant for: AbbVie, Celgene, Janssen, Chugai, Lilly, Novartis, Pfizer, MSD, and UCB, Speakers bureau: AbbVie, Celgene, Janssen, Chugai, Lilly, Novartis, Pfizer, MSD, and UCB, P. Zueger Employee of: AbbVie, J. Kalabic Employee of: AbbVie, M. Wu Employee of: AbbVie, I. Lagunes Galindo Employee of: AbbVie, F. Van den Bosch Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB